The Abitinian Martyrs and the Outbreak of the Donatist Schism - Dearn, Alan (The journal of ecclesiastical history, 2004)
It is often claimed that the story of the Abitinian martyrs provides evidence relevant to the outbreak of the Donatist schism. However, this interpretation of the text rests upon a number of false assumptions regarding its manuscript tradition and the celebrity of the martyrs it commemorates. Rather than being written in the early fourth century, the text in its extant form was probably written after the Council of Carthage in 411, and perhaps in response to it. It thus does not cast light upon the outbreak of the schism, but rather on the way in which the events of the early fourth century were polemically reinterpreted at a much later date.